Contribution of ICF on the functionality of individuals with chronic low back pain - Santos, Bárbara Cordeiro; Scharan, Karoleen Oswald; Fontana, Mariane Benicio; Moser, Auristela Duarte de Lima (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: The use of the International Classification of Functioning, Disability and Health (ICF) in clinical settings has been emphasized with the objective of establishing a standardized language among professionals, as well as to collect and interpret related results to health and states related to it in different cultures from a biopsychosocial perspective. Objective: To define the functional profile of from patients with chronic low back pain based on the International Classification of functioning, disabilities and health (ICF). Method: During February-March of 2014 a functional questionnaire based on the ICF was applied for 42 adults. Results: The mean age was 47.8 (± 16.9) years, with predominance of women (69%). Two categories and one subcategory represented higher percentage of difficulty: Using transport (54.8%), Household tasks (62.5%) and Bending (69.1%). In Environmental Factors, 50% of the sample reported having difficulty accessing public environments. The categories of self-care domain did not show high percentage of difficulty. Conclusion: The use of the functional questionnaire was able to determine the functional profile of the subjects, contributing to subsidize interventions in a program of Back School. Approaches may be more targeted based on codes where there were greater difficulties and may be more specific to participants daily life.